Penyuluhan, Pencatatan Status Imunisasi Balita dan Peningkatan Komunikasi-Koordinasi dengan Pihak Desa Dalam Upaya Menurunkan Kasus Campak di Desa G, Wilayah Kerja Puskesmas P, Kabupaten Tangerang, Provinsi Banten - Nasyidatul Ulya; Dewi Novianti; Aliawati Albek (Universitas Pahlawan Tuanku Tambusai, 2026)
Measles remains a significant public health problem in Indonesia, with an observed increase in cases following the COVID-19 pandemic, partly attributed to a decline in immunization coverage. This Community Diagnosis Study was conducted in Village G, within the working area of Primary Health Center P, Tangerang District, from December 12, 2025, to January 8, 2026. A total of 38 suspected measles cases were recorded between June and November 2025, showing an increasing monthly trend, with the highest number of cases reported in Village G. In the initial stage, priority setting was conducted using the USG (Urgency, Seriousness, Growth) scoring method, followed by problem analysis using the BLUM Paradigm. Prioritization of contributing factors was further determined using a non-scoring Delbecq technique, which identified the lifestyle factor as the priority domain for further analysis using Fishbone Diagram and the 5 Whys method. The root causes identified included: (1) suboptimal measles health education activities; (2) incomplete documentation of measles immunization status among children under five; and (3) limited communication and coordination between Primary Health Center P and Village G authorities.Three interventions were implemented: measles health education sessions, improvement of immunization status recording for under-five children, and strengthening communication and coordination with Village G stakeholders. The evaluation showed that 90.9% of participants met the passing criteria (post-test score ≥70 and an improvement in knowledge of at least 10 points). Additionally, 83.3% of participants were found to be unvaccinated for measles, and communication and coordination between the health center and village cadres were successfully strengthened. This program demonstrated improvements in participants’ knowledge regarding measles, enhanced identification of immunization status, and improved communication and coordination between the health center and village authorities. Continuous health education, catch-up immunization programs, and advocacy to Village G officials are recommended as follow-up strategies. Through these efforts, it is expected that measles immunization coverage will increase, ultimately contributing to a reduction in measles morbidity and mortality in the working area of Primary Health Center P, including Village G, in the medium and long term.